The Effect of Modifying the C9 Position of Fluorene with N-Donor Substituents on Selected Physicochemical Properties - Paweł Kalarus; Agata Szlapa-Kula; Michał Filapek; Sławomir Kula (Molecules)
Fluorene has been an extremely valued building block for many chemical compounds for a number of years. As a result, it is possible to design and obtain compounds with precisely defined physicochemical properties adapted to selected applications. An extremely interesting derivative of fluorene, which has been enjoying increasing interest in recent years, is dibenzofulvene (DBF) and its further structural modifications. So far, a number of dibenzofulvene derivatives have been described in the literature. Many of the presented DBFs are extremely structurally complex, which is why the influence of substituents on the physicochemical properties of the final compounds is not easy to determine unequivocally. Therefore, in this article, an attempt was made to explain the influence of N-donor substituents on selected physicochemical properties of dibenzofulvene derivatives (A-1–A-6). Moreover, these properties were compared to the results obtained for unsubstituted fluorene. The studies conducted showed that small modifications of the fluorene structure towards dibenzofulvene derivatives significantly change the absorption and emission properties of the final compounds. Importantly, the abovementioned structural modifications strongly affect the electrochemical properties, significantly reducing the energy gap and causing the oxidation potential to decrease to 0.18–0.42 V. Moreover, the process itself becomes fully reversible. The experimentally determined values coincide with those obtained theoretically via DFT calculations.